An Analysis of the Linkages Between Fishermen and Extension Personnel in Marine Fisheries in Kerala - Immanuel, Sheela; K., Kanagasabapathy; S., Balasubramaniam (Fishery Technology, 2025)
In marine fisheries the linkages between the fishermen and the extension system play an important role in technology transfer and its adoption. Research studies on linkages inmarine fisheries are very limited. So tbis study was taken up to find out the linkage activities through which both the systems are contacting each other. It was found that 60 % of the fishermen had medium level of linkage of with the extension personnel followed by low (21.33%) and high (19.34%) linkage level. The paper also highlights the frequency of linkage and the level of perception about linkages between the two systems. The paper implies that the linkage activities need to be enhanced so as to derive an overall development in the fisheries sector.